Total Hip Lithiasis: A Rare Sequelae of Spilled Gallstones - Vineet Tyagi; Daniel H. Wiznia; Adrian K. Wyllie; Kristaps J. Keggi (Case Reports in Orthopedics)
Laparoscopic cholecystectomy is a surgical treatment for acute cholecystitis or symptomatic cholelithiasis. One potential complication, the spillage of gallstones into the peritoneal cavity, can form a nidus for infection and may be associated with hepatic, retroperitoneal, thoracic, and abdominal wall abscesses. We report a case of a patient presenting with a right iliopsoas abscess and an infected right hip prosthesis status postlaparoscopic cholecystectomy. A CT demonstrated that the acetabular shell was overmedialized and perforated through the medial wall. The patient was taken to the operating room for explantation of components. A collection of gallstones was identified deep to the acetabulum during the explantation. The case highlights the importance of avoiding overmedialization of the acetabular component, which can provide a direct route for infection into the hip joint.